Electrodeposition of CoNi Cocatalyst to Enhance Ethanol Electrooxidation of Zn-doped Cu2O-Cu Photocatalyst - Alfian Putra Utama; Afrizal (Pusat Inovasi Sains, 2023)
In this research, the electrooxidation of ethanol was catalyzed using Zn-doped Cu2O-Cu/CoNi heterostructure syntesized using an electrodeposition method. Potential deposition of CoNi cocatalyst was varied to obtain the highest photoelectrochemical performance and photocatalytic activity of Zn-doped Cu2O-Cu/CoNi. The photoelectrochemical properties and photocatalytic activity investigated by electrochemical impedance spectroscopy, linear sweep voltammetry, and cyclic voltammetry. The increase of deposition potential from -1.3 V to -1.75 V increased the ethanol oxidation reaction. Zn-doped Cu2O-Cu/CoNi -1.75 V electrode showed superior photocatalytic activity for the ethanol electrooxidation compared to other electrodes. This photocatalyst showed a high photocurrent density of 22.47 mA/cm2. Moreover, cyclic voltammetry tests up to 100 cycles indicated that CoNi deposition potential at -2 V increased the long-term stability of the photocatalyst against the poisoning species than other electrodes. The fraction of CoNi enhanced CO tolerance and contributed to the higher specific activity towards ethanol electrooxidation. An excess number of CoNi at -2 V was found to decrease photocatalytic activity but increase the photostability of the material.